2012
DOI: 10.1007/s00228-012-1456-6
|View full text |Cite
|
Sign up to set email alerts
|

Bioequivalence between generic tacrolimus products marketed in Spain by adjusted indirect comparison

Abstract: Not only are the generic products bioequivalent with the reference product, but also with each other.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 14 publications
5
27
0
Order By: Relevance
“…The authors concluded that even with the Bworse^scenario of 9.5 % non-bioequivalent products, this low value provides reassurance of the BE of two generic products that have been shown to be bioequivalent to the same reference product. However, this does not seem to be the worst scenario, but a very favorable one, because point estimate differences between generics can be larger [5,16]. Karalis et al (2013) plotted the probability of accepting BE between generics as a function of their point estimates and concluded that although two generics are bioequivalent to the reference product, this does not ensure that they are bioequivalent to one another [8].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The authors concluded that even with the Bworse^scenario of 9.5 % non-bioequivalent products, this low value provides reassurance of the BE of two generic products that have been shown to be bioequivalent to the same reference product. However, this does not seem to be the worst scenario, but a very favorable one, because point estimate differences between generics can be larger [5,16]. Karalis et al (2013) plotted the probability of accepting BE between generics as a function of their point estimates and concluded that although two generics are bioequivalent to the reference product, this does not ensure that they are bioequivalent to one another [8].…”
Section: Discussionmentioning
confidence: 94%
“…Combining 57 possible differences between point estimates from 0 to 14 % in 0.25 % increments and 16 14,592 scenarios were computed, although some scenarios were repetitive (e.g., where the first study has 80 % power and the second has 90 % power is the same scenario as where the first study has 90 % power and the second one has 80 % power).…”
Section: Computed Scenariosmentioning
confidence: 99%
“…However, since 2010, the European Medicines Agency (EMA) has stipulated that for bioequivalence to be demonstrated for drugs like tacrolimus that have a narrow therapeutic index, pharmacokinetic parameters should lie within 90-111% of the innovator drug (3). Despite the fact that it is well known that the pharmacokinetic properties of tacrolimus are affected by a number of patient related variables, such as gut function, concomitant medication, and liver function, there is as yet no requirement for bioequivalence to be demonstrated in patients, nor does bioequivalence need to be demonstrated between different generic formulations of the same drug (4). Therefore, for dose critical drugs, such as tacrolimus, where maintenance of stable levels is imperative to ensure stable graft function and avoid complications, there is a need to demonstrate similar clinical outcomes with the use of generic vs. innovator formulations (5).…”
mentioning
confidence: 97%
“…3 Generic drugs have been used in a variety of ways, such as cardiovascular medicines, anticonvulsant medicines, nonsteroidal anti-inflammatory drugs, levothyroxine, oral contraceptives, and proton pump inhibitors. [4][5][6][7][8] This trend is also true for the antiglaucoma ophthalmic solutions. [9][10][11] The 2% dorzolamide/0.5% timolol fixed-combination (DTFC) drug has been widely used for the treatment of glaucoma because of its highly intraocular pressure (IOP)-lowering effect and the increased compliance with it due to its ease of use.…”
Section: Introductionmentioning
confidence: 68%